2012
DOI: 10.1111/j.1748-0361.2012.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Addressing Barriers to Implementation of Environmental and Policy Interventions to Support Physical Activity and Healthy Eating in Rural Communities

Abstract: PURPOSE Rural residents are at greater risk of obesity than urban and suburban residents. Failure to meet physical activity and healthy eating recommendations play a role. Emerging evidence shows the effectiveness of environmental and policy interventions to promote physical activity and healthy eating. Yet most of the evidence comes from urban and suburban communities. The objectives of this study were to 1) identify types of environmental and policy interventions being implemented in rural communities to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 27 publications
(49 reference statements)
5
109
0
1
Order By: Relevance
“…26,27 Additionally, in areas where there are no parks and where schools are farther from homes, places such as green or open spaces could be used for physical activities where youth can engage in structured or free play. 28 For those in urban areas with access to parks, using available park programming, amenities, and safety improvements could increase the use of parks for physical activity. 4 In conclusion, this study found that more than half of U.S. school-age youth live in a block group within half a mile of a park.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Additionally, in areas where there are no parks and where schools are farther from homes, places such as green or open spaces could be used for physical activities where youth can engage in structured or free play. 28 For those in urban areas with access to parks, using available park programming, amenities, and safety improvements could increase the use of parks for physical activity. 4 In conclusion, this study found that more than half of U.S. school-age youth live in a block group within half a mile of a park.…”
Section: Discussionmentioning
confidence: 99%
“…Others have identified a lack of adequate staff and expertise in the built environment or in other wellness areas [93]. Additionally, the built environment is often seen as an amenity rather than a necessity by rural community members [93].…”
Section: Partnershipsmentioning
confidence: 99%
“…Additionally, the built environment is often seen as an amenity rather than a necessity by rural community members [93]. Therefore, strong public participation and buy-in, collaboration, and input are needed from community members and leaders, partners, and stakeholders [93][94][95], including mayors, town planners, public works departments, recreation department staff, school officials, church leaders, business owners, health care and public health professionals, architects, parents, senior citizens, and youth.…”
Section: Partnershipsmentioning
confidence: 99%
“…Lack of programmatic activities and social connections appear to be important correlates, but these are potentially the most resistant to intervention in rural settings. 93,94 In the most recent rural-specific review examining the relationship between the social and physical environments and PA in adults, Frost and colleagues 2 found that aesthetics and civilities, perceived safety (from crime or traffic), and the presence of parks, trails, and recreation facilities were most consistently associated with PA in rural adults. The associations between sidewalks or traffic density and PA, which are consistently associated with PA in urban adults, were not consistently associated with PA in rural adults.…”
Section: Multi-level Environmentsmentioning
confidence: 99%